Inventory and analysis of the Black Vermillion river system riparian corridors - Sass, Christopher Kevin (Kansas State University, 2008)
The purpose of the investigation was to inventory and analyze riparian corridor vegetation changes throughout the Black Vermillion watershed from approximately 1857 through 2007. Three sub-watersheds were studied; North Fork, Irish Creek and Black Vermillion Main Stem. Research questions investigated were: 1) What changes in riparian corridor width have taken place since the original territory surveys done in 1857 and why? 2) How has land cover adjacent to riparian corridors changed since the original territory surveys? 3) Has woody species composition in the riparian corridors changed? The research questions were addressed using a variety of techniques and tools including aerial photography, basic GIS, and vegetation survey techniques. Territory of Kansas survey maps and notes that were completed in 1857 were used as baseline reference conditions concerning corridor width and woody species present in the riparian corridors. Inventory and analysis of the riparian vegetation change over time and adjacent land cover will aid in understanding the present ecology of these riparian corridors and are important to stream and riparian ecosystem rehabilitation. Woody riparian corridors increased in width throughout the watershed from 1857 until about 1956 (probably due to a decrease in prescribed burning and lack of grazing), which is the pre-channelization period for this watershed. After channelization (late 1960's & early 1970's), average corridor widths dropped significantly as the stream was shortened a total of 15.8 miles (25.4Km). Most often, the land cover changed from native, tallgrass prairie to cultivated cropland or pasture. Woody species composition has changed over time from established mature woodland to a pioneer successional stage. The findings of this study can influence beginning stages of design for natural habitat rehabilitation purposes in this watershed. Design decisions for land rehabilitation purposes should consider reference conditions (historic), and to understand reference conditions we must study the history of land use and land change. This study provides a template for studying the history of land use and land use change of riparian corridors for Midwestern, agricultural landscapes.
Keywords: Riparian; Corridor; Channelization; Black Vermillion; Landscape Architecture (0390)